Modal Sosial dalam Pengembangan Wisata Nangkula Park di Desa Kendalbulur, Kabupaten Tulungagung - Rizqi Nur Rizna Fitria Ningsih; Nanda Harda Pratama Meiji (Jurnal Sosiologi USK (Media Pemikiran & Aplikasi), 2023)
This study aims to identify the development of Nangkula Park tourism, including the constraints and social capital within the community-based tourism group (Pokdarwis). The study employs a qualitative descriptive method. Data were collected through observation, interviews, and documentation. The research findings indicate that the development of Nangkula Park tourism by Pokdarwis is achieved through the establishment of artificial tourism with comprehensive facilities. The constraints identified within Pokdarwis regarding the development of Nangkula Park tourism are related to (1) Pokdarwis' human resources, (2) limited funds, and (3) varying levels of participation. Meanwhile, the forms of social capital possessed by Pokdarwis Nangkula Park include (1) social norms formed from community values, which give rise to unwritten rules that are consistently followed, (2) trust expressed through mutual assistance and trust in the division of labor, and (3) social networks established with various parties such as the tourism department and other Pokdarwis groups.AbstrakKajian ini berupaya mengidentifikasi pengembangan wisata Nangkula Park, termasuk kendala dan modal sosial dalam kelompok sadar wisata (Pokdarwis). Kajian ini menggunakan metode kualitatif model deskriptif. Data dikumpulkan melalui observasi, wawancara, dan dokumentasi. Temuan penelitian menunjukkan bahwa pengembangan wisata Nangkula Park yang dilakukan oleh Pokdarwis adalah dengan mewujudkan wisata buatan dengan fasilitas yang lengkap. Kendala yang ditemukan dalam Pokdarwis terhadap pengembangan wisata Nangkula Park adalah terkait dengan (1) SDM Pokdarwis, (2) dana yang terbatas, (3) tingkat partisipasi yang berbeda. Sementara itu, bentuk modal sosial yang dimiliki Pokdarwis Nangkula Park meliputi (1) norma terbentuk dari nilai-nilai sosial bermasyarakat, darinya lahir aturan-aturan tidak tertulis dan selalu dipatuhi. (2) kepercayaan dituangkan dalam bentuk saling menolong serta kepercayaan dalam pembagian kerja. (3) jaringan sosial terjalin dengan berbagai pihak seperti dinas pariwisata, dan pokdarwis lain.